Sejong Korean Conversation 1 = 세종한국어 회화 1 (Kong & Park, 2018)
Sejong Korean Conversation is designed with the purpose of helping Korean language learners at The King Sejong Institute(KSI) to develop practical Korean language skills, especially focusing on conversation, listening, and communication skills. Aims and Approaches The purpose of this textbook is to provide Korean language learners a reciprocal understanding of Korean language and Korean society, based on the foundation and objectives of the establishment of the King Sejong Institute. This textbook is based on the International Standard Curriculum for Korean Language and the KSI Standard Model of Education.